p8/nupr1 regulates DNA-repair activity after double-strand gamma irradiation-induced DNA damage - Gironella, Meritxell (2009)
The stress protein p8 is a small, highly basic, unfolded, and multifunctional protein. We have previously shown that most of its functions are exerted through interactions with other proteins, whose activities are thereby enhanced or repressed. In this work we describe another example of such mechanism, by which p8 binds and negatively regulates MSL1, a histone acetyl transferase (HAT)-associated protein, which in turn binds the DNA-damage-associated 53BP1 protein to facilitate DNA repair following DNA gamma-irradiation. Contrary to the HAT-associated activity, MSL1-dependent DNA-repair activity is almost completely dependent on 53BP1 expression. The picture that has emerged from our findings is that 53BP1 could be a scaffold that gets the HAT MSL1-dependent DNA-repair activity to the sites of DNA damage. Finally, we also found that, although p8 expression is transiently activated after gamma-irradiation, it is eventually submitted to sustained down-regulation, presumably to allow development of MSL1-associated DNA-repair activity. We conclude that interaction of MSL1 with 53BP1 brings MSL1-dependent HAT activity to the vicinity of damaged DNA. MSL1-dependent HAT activity, which is negatively regulated by the stress protein p8, induces chromatin remodeling and relaxation allowing access to DNA of the repair machinery